Role of magnetic resonance spectroscopy in grading of gliomas- a tertiary care centre study - S., Ajitha J.; Jose, Teena; G., Unnikrishnan (International Journal of Research in Medical Sciences, 2022)
Background: Grading of gliomas is important for the determination of appropriate treatment strategies. MR spectroscopy has found increasing utility in grading of gliomas. Methods: MR spectroscopic imaging was done for the referred patients to obtain Cho/NAA and Cho/Cr ratios. After analyzing histopathology reports, gliomas were classified into low grade and high grade. Histologically proven 54 low grade and 54 high grade gliomas were included in the study. The mean and standard deviation of these variables were obtained and compared between two groups. ROC curve analyses were performed in order to identify the optimal cut-off value for metabolite ratios for prediction purposes of high grade versus low grade gliomas. Results: The mean and SD of Cho/NAA ratio in low grade glioma was 1.93±1.19. The mean and SD of Cho /NAA ratio in high grade glioma was 3.16±1.73 was significantly higher. The optimal cut-off for differentiating low grade and high grade gliomas was 2.15 with a sensitivity of 74.07% and specificity of 66.67%. The mean and SD of CHO/Cr in low grade glioma was 2.05±0.76. The mean and SD of Cho/NAA in high grade glioma was 2.87±1.65 was significantly higher. The optimal cut-off for differentiating low grade and high grade gliomas was 1.98 with a sensitivity of 64.8% and specificity of 64.1%. Conclusions: MR spectroscopy imaging plays a pivotal role in prediction of glioma grade preoperatively and helps in deciding appropriate treatment strategies.